Optimal Portfolio Risk Estimation Using Expected Shortfall of Jakarta Islamic Index (JII) Shares - Lestari, Adika Risky; Sari, Devni Prima (Universitas Negeri Padang, 2024)
Forming an optimal portfolio using the Mean-Variance method with Downside Deviation as a measure of risk produces a good combination of assets. Before investing, estimating risk as a worst-case scenario is very important. Expected shortfall (ES) serves as a risk measure that takes into account the possibility of losses that exceed Value at Risk (VaR). This study aims to determine the optimal portfolio and compare ES and VaR at the 90%, 95%, and 99% confidence levels. This research data involves 3 stocks namely ACES, WIFI, and TLKM. Based on the results of the analysis conducted, the optimal combination of weights is ACES (19%), WIFI (10%), and TLKM (71%). Comparison of ES and VaR shows that the higher the level of confidence, the higher the VaR and ES values generated, so the greater the risk that will be borne by investors and the capital allocation used to cover these losses.